Kontribusi Pondok Pesantren Syekh Muhammad Dahlan Aek Hayuara Terhadap Pendidikan Islam di Sibuhuan Kabupaten Padang Lawas, 1938-1973 - Nasution, Rapita Sari; Siregar, Yusra Dewi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Pesantren Sheikh Muhammad Dahlan Aek Hayuara, founded in 1938 by Sheikh Muhammad Dahlan Hasibuan, is recognized as the oldest Islamic boarding school in Padang Lawas district and the progenitor of all pesantren in Sibuhuan. This study explores the historical development and contributions of this pesantren to Islamic education and broader societal dimensions including economics, religion, social life, and the struggle for independence in Sibuhuan. Employing a qualitative research approach, data were gathered through interviews, field observations, and documentation, complemented by a literature review encompassing books, archival materials, institutional documents, and relevant scholarly sources. The findings reveal that the pesantren has played a pivotal role in shaping Islamic education in the region, having produced numerous Islamic scholars and community leaders across various sectors. Its existence not only laid the foundation for the emergence of other pesantren but also contributed significantly to the educational, religious, and sociocultural landscape of Padang Lawas. The pesantren's legacy continues to influence Islamic learning and community empowerment, confirming its status as a central institution in the historical and educational narrative of Sibuhuan.